Tying Mango tree branch to the entrance - Mumbai Archive Project Team (Jio Institute, 2024)
The mama (maternal uncle) of the bride brings a mango tree cutting and ties it to the entrance. Mango leaves are regarded as symbols of purity, fertility and abundance. The presence of the mango tree is believed to bring blessings for a fruitful and prosperous married life for the newlyweds.